The Analyss Of Promo’s Implementation To IncreaseThe Purchase Interest Study Case At Niwa Garden Coffee Shop - Astrid Nissi Romatua; Arianis Chan; Pratami Wulan Tresna; Cecep SafaatulBarkah (International Journal Of Community Service, 2023)
Niwa Garden is a coffee shop located in the city of Malang, East Java. This coffee shop hasbeen around for almost three years. Having a daily income that can be saidto be quite large forMSMEs, lately, Niwa Garden has experienced a decline in sales.There are so many peoplewho are in the location of the coffee shop, but little incomeis received. After being traced, it turns out that there are several people who are members of a consumer group who do notmake purchases, but still use the facilities provided by the coffee shop. Seeing this, an alternative solution to the problem was found by implementing bundling promos, which are specifically for consumers who come in groups. This research was conducted to explain whether the application of promos to products can increase consumers' purchase requests,thereby influencingtheir purchasing decisions. This resource is intended to explain the affect of promo toward purchase interest, include the influence of promo to increase purchaseinterest that related to purchase decision.